Design an Inverter for Residential Wind Generator - Riza Muhida; Afzeri Tamsir; Rudi Irawan; Ahmad Firdaus A. Zaidi (Bandar Lampung University (UBL), 2012)
As one of alternative source of renewable energy, wind energy has an excellence prospect in Indonesia, particularly in coastal and hilly areas that has potential wind to generate electricity for residential use. There is urgent need to locally develop the low cost inverter of wind generator system for residential use. Recent developments of power electronic converters and embedded computing allow improvement of power electronic converter devices that enable integration of microcontrollers in its design. In this project, an inverter circuit with suitable control scheme design was developed. The circuit was to be used with a selected topology of Wind Energy Conversion System (WECS) to convert electricity generated by 500W direct-drive permanent magnet type wind generator which is typical for residential use. From single phase AC output of the generator, rectifier circuit is designed to convert AC to DC voltage. Then DC-DC boost converter was used to step up the voltage to a nominal DC voltage suitable for domestic use. The proposed inverter then will convert the DC voltage to sinusoidal AC. The duty cycle of sinusoidal Pulse-Width Modulated (SPWM) signal controlling switches in the inverter was generated by a microcontroller. The lab-scale experimental rig involves simulation wind of wind generator by running geared DC motor coupled with 500W wind generator where the prototype circuit was connected at generator output. Experimental circuit produced output voltage single phase 240V sinusoidal AC voltage with frequency of 50Hz. Measured total harmonics distortion (THD) of the voltage across load was 4.0% which is within limit of 5% as recommended by IEEE Standard 519-1992.